(untitled) (Journal of Libya for geographical studies, 2022)
The research aims to estimate the volume of surface runoff of the Wadi Tilal Basin, by analyzing and processing the digital elevation model (DEM) data extracted from (ASTER) satellite visuals with a resolution of (30) meters, by employing (GIS) software to extract some morphometric characteristics. And the hydrology of the basin of Wadi Tilal, which has an area of ​​(6335) km², and then to determine the volume of the torrential flow for the day (25) October (1972) AD as a case study in the region. The research concluded that the surface runoff volume in the Wadi Tilal basin was about (628432)m³, and the net surface runoff was about (611502.04)m³. Which is an designation of the riskiness of the basin.